Design, synthesis and anticancer evaluation of 3-methyl-1H-indazole derivatives as novel selective bromodomain-containing protein 4 inhibitors. (1st February 2022) - Dong, Ru; Zhang, Cheng; Wang, Chao; Zhou, Xin; Li, Wen; Zhang, Jin-Yang; Wang, Min; Xu, Yong; Sun, Li-Ping
Graphical abstract: Abstract: Bromodomain-containing Protein 4 (BRD4), an 'epigenetic reader', regulates chromatin structure and gene expression via recognizing and binding acetylated lysine in histones. BRD4 has become a therapeutic target for cancers because it promotes the expression of the tumor genes, such as c-Myc, NF-κB, and Bcl-2. In this study, a new series of 3-methyl-1 H -indazole derivatives were designed via virtual screening and structure-based optimization. All compounds were synthesized and evaluated for their inhibitory activities to BRD4-BD1 and their antiproliferative effects in cancer cell lines. Among them, several compounds (such as 9d, 9u and 9w ) exhibited strong BRD4-BD1 affinities and inhibition activities, and potently suppressed MV4;11 cancer cell line proliferation. Among them, compound 9d showed excellent selectivity for BRD4 and effectively suppressed c-Myc, the downstream protein of BRD4. This study provided new lead compounds for further biological evaluation on BRD4.